The incidence and patterns of illness at the Sochi 2014 Winter Paralympic Games: a prospective cohort study of 6564 athlete days. Issue 17 (9th May 2016) - Derman, W; Schwellnus, M P; Jordaan, E; Runciman, P; Van de Vliet, P; Blauwet, C; Webborn, N; Willick, S; Stomphorst, J
Abstract : Objective: To describe the epidemiology of illness at the Sochi 2014 Winter Paralympic Games. Methods: A total of 547 athletes from 45 countries were monitored daily for 12 days over the Sochi 2014 Winter Paralympic Games (6564 athlete days). Illness data were obtained daily from teams without their own medical support (13 teams, 37 athletes) and teams with their own medical support (32 teams, 510 athletes) through electronic data capturing systems. Results: The total number of illnesses reported was 123, with an illness incidence rate (IR) of 18.7 per 1000 athlete days (95% CI 15.1% to 23.2%). The highest IR was reported for wheelchair curling (IR of 20.0 (95% CI 10.1% to 39.6%)). Illnesses in the respiratory system (IR of 5.6 (95% CI 3.8% to 8.0%)), eye and adnexa (IR of 2.7 (95% CI 1.7% to 4.4%)) and digestive system (IR of 2.4 (95% CI 1.4% to 4.2%)) were the most common. Older athletes (35–63 years) had a significantly higher IR than younger athletes (14–25 years, p=0.049). Conclusions: The results of this study indicate that Paralympic athletes report higher illness incidence rates compared to Olympic athletes at similar competitions. The highest rates of illness were reported for the respiratory and digestive systems, eye and adnexa, respectively. Thus, the results of this study form a basis for the identification of physiological systems at higher risk of illness, which can in turn inform illness prevention and management programmes with eventual policy change to promote athlete safety in future editions of the Winter Paralympic Games.